Sasanian Cities Historical and Archaeological Perspectives - Meysam Labbaf-haniky (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Cities as the cradles of social relations are considered as the significant phenomena in historical and archaeological point of views. Establishing the earliest cities, therefore, has been regarded as a crucial step in the evolution process of the societies. The Sasanian cities, presenting the complicated form of the cities during the late antiquity, have been investigated by Reza Mehrafarin in the book entitled ‘Sasanian Cities’. The book, including worthwhile information about some Sasanian cities, has been compiled after the published reports, articles, and books. Nevertheless, like other scientific works, the book contains some major shortcomings in the coverage of the relevant publications and some minor shortcomings  in its content.